Miliary Mesothelioma - Dujinthan Jayabalan; Michaela Donaghy; Chloe Charlesworth; Edward Fysh; Y. C. Gary Lee (Respirology Case Reports)
ABSTRACT Miliary spread of mesothelioma is a rare but important manifestation of late‐stage disease, likely due to hematogenous dissemination. This case highlights characteristic CT imaging findings, emphasizing the need for awareness among clinicians and radiologists. Recognizing this pattern can aid in diagnosis, prognostication, and appropriate referral for palliative management.